Suicide rates declined in China: The social, cultural and economic factors - Jie Zhang (Archives of Preventive Medicine - Peertechz Publications, 2020)
The suicide rates in the world have been growing in the past century [1] and the rates in the United States have rapidly increased by about 33%, from 10.5 per 100,000 population in 1999 to 14.0 in 2017 [2], regardless of prevention efforts with affluent funding [3]. On the other hand, the overall suicide rate in China has decreased from 23.0/100,000 in 1999 to 8.6/100,000 in 2017, marking a 63% drop over past two decades [4]. The most marked decrease has been observed in young women in rural areas under 35 years of age, whose suicide rate appears to have dropped by as much as 90% [4].